Clean Water and Sanitation Issues: Freeport Tailing Case - Nasywa Izra; Zahwa Aulia Nurul ‘Aini; Keysha Valeriena Sachenka Whira Andini (Jurnal Riksa Cendikia Nusantara, 2025)
Access to clean water and proper sanitation is a basic human right as stated in Sustainable Development Goal 6. However, achieving this goal still faces serious challenges in areas with large-scale extractive industries, one of which is in Papua due to the management of tailings by PT Freeport Indonesia. This study aims to analyze the impact of tailings management on water quality and sanitation, particularly in the Ajkwa river basin, and its implications for the fulfillment of SDG 6 for indigenous peoples. This study uses a qualitative approach with a descriptive case study method based on secondary data obtained from government reports, company documents, scientific journals, and civil society organization publications. The results of this study show that the disposal of large amounts of tailings has caused a decline in water quality, changes in river and coastal ecosystems, and made it difficult for indigenous peoples to access clean water and safe sanitation. These conditions reflect weak environmental governance, power imbalances between the state, multinational corporations, and local communities, as well as the suboptimal implementation of sustainable development commitments. Therefore, strengthening environmental monitoring, data transparency, and meaningful engagement of indigenous peoples are crucial steps in restoring water quality and achieving SDG 6 in Papua.